Modes of vibration and sound radiation from the HANG - MORRISON, Andrew; ROSSING, Thomas (Archives of Acoustics, 2007)
The HANG is a new hand-played steel instrument developed by PANArt in Switzerland. We describe the modes of vibration, observed by holographic interferometry and the sound radiation from the instrument observed by measuring the sound intensity in an anechoic room by the two-microphone method. A low-voice HANG is compared with a high-voice HANG.